History of the Book - Ömer Dalkıran (Türk Kütüphaneciliği)
Undoubtedly the most basic element is information in the development of civilization. In this context it is obvious the importance of the book as a information source. The book showed different levels of development early ages up to this day. The emergence and development of the book shaped various cultural, political, economic, and geographic factors. Today, the book been in existence in both print and electro- nic formats and continues to be the main information source. To know the history of the book will shed light on future assessments. In this context, the aim of this study to present an overview the formation and development of the printed book in the historical process.